Sacrifice in Kierkegaard's Fear and Trembling - Crocker, Sylvia Fleming (Harvard theological review, 1975)
In Kierkegaard's hands the story of Abraham and Isaac is clearly a story about the relationship between the life of sacrifice and the religious life. By leading us on to deeper and deeper levels of sacrifice, he aims to make us grasp the essential nature of faith and, with it, the right relationship between the individual and God. He does this by means of a dialectic involving Abraham's response to God in contrast to (1) the other possible responses he might have made, and (2) Kierkegaard's own response to what he believed was the divine command to break his engagement to Regina Olsen.